2020
DOI: 10.3390/fi12070120
|View full text |Cite
|
Sign up to set email alerts
|

A Decoding-Complexity and Rate-Controlled Video-Coding Algorithm for HEVC

Abstract: Video playback on mobile consumer electronic (CE) devices is plagued by fluctuations in the network bandwidth and by limitations in processing and energy availability at the individual devices. Seen as a potential solution, the state-of-the-art adaptive streaming mechanisms address the first aspect, yet the efficient control of the decoding-complexity and the energy use when decoding the video remain unaddressed. The quality of experience (QoE) of the end-users’ experiences, however, depends on the capability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The complexity of the decoder affects the compression performance [14], [61]. To explore the influence of the complexity of the video reconstruction network in our proposed framework on the performance of video compression, we perform another experiment by replacing the video reconstruction network which is made up of two cascaded U-Nets with one U-Net, two residual blocks, and one residual block.…”
Section: Influence Of the Complexity Of The Video Reconstruction Networkmentioning
confidence: 99%
“…The complexity of the decoder affects the compression performance [14], [61]. To explore the influence of the complexity of the video reconstruction network in our proposed framework on the performance of video compression, we perform another experiment by replacing the video reconstruction network which is made up of two cascaded U-Nets with one U-Net, two residual blocks, and one residual block.…”
Section: Influence Of the Complexity Of The Video Reconstruction Networkmentioning
confidence: 99%
“…The third paper [8], written by Thanuja Mallikarachchi, Dumidu Talagala, Hemantha Kodikara Arachchi, Chaminda Hewage and Anil Fernando, identifies the importance of addressing the control of decoding complexity and energy use when decoding video to improve user QoE. As a solution, this study proposes an encoding framework that is capable of generating video bit streams with arbitrary bit rate and decoding complexity levels using a decoding complexity rate distortion model.…”
Section: Contributionsmentioning
confidence: 99%
“…Concerning the latter, certain studies revealed that the decoder is a major reason for a high energy consumption in portable devices such as smartphones or tablet PCs [7,12], especially if software decoding is used [16,19]. As a consequence, various studies focused on reducing the energy consumption of video decoders [8,11,13,26] while keeping the visual quality of the video. Also for the encoder, various studies focus on the energy consumption or the complexity [28,33,39] in order to obtain a high compression while using little energy resources.…”
Section: Introductionmentioning
confidence: 99%